Effect of cytoplasmic fragmentation on embryo development, quality, and pregnancy outcome: a systematic review of the literature - Ariella Yazdani; Iman Halvaei; Catherine Boniface; Navid Esfandiari (BMC, 2024)
Abstract The role of cytoplasmic fragmentation in human embryo development and reproductive potential is widely recognized, albeit without standard definition nor agreed upon implication. While fragmentation is best understood to be a natural process across species, the origin of fragmentation remains incompletely understood and likely multifactorial. Several factors including embryo culture condition, gamete quality, aneuploidy, and abnormal cytokinesis seem to have important role in the etiology of cytoplasmic fragmentation. Fragmentation reduces the volume of cytoplasm and depletes embryo of essential organelles and regulatory proteins, compromising the developmental potential of the embryo. While it has been shown that degree of fragmentation and embryo implantation potential are inversely proportional, the degree, pattern, and distribution of fragmentation as it relates to pregnancy outcome is debated in the literature. This review highlights some of the challenges in analysis of fragmentation, while revealing trends in our evolving knowledge of how fragmentation may relate to functional development of the human embryos, implantation, and pregnancy outcome.